Human space medicine: Physiological performance and countermeasures to improve the astronaut's health: Medicina humana espacial: Performance fisiológico y contramedidas para mejorar la salud del astronauta - V. Rivera, Milton (2020)
This Review Article is presented based on current scientific evidence on space medicine focused on human physiology and its countermeasures. Therefore, a non-systematic bibliographic search of scientific articles and research books in English-Spanish of the last 7 years was carried out, detailing their application in humans, murine models and in vitro experiments. The conditions of the space environment such as microgravity and radiation that produce considerable physiological changes in the cardiovascular system (redistribution of fluids, cardiovascular remodeling, arrhythmias) were taken into account; nervous (sensorimotor, neurosensory, neurovestibular); respiratory (volume and capacity changes); renal (lithiasis); musculoskeletal (muscular atrophy, osteoporosis); hematological (anemia); immunological (immune dysregulation) and digestive (intestinal microbiota disorder). In addition, there are biological, molecular and genetic processes still to be explored, in order to know and mitigate the uncertain mechanisms triggered in extreme and dangerous environments. Therefore, it is a priority to develop and implement countermeasures to reduce the harmful effects on health, with the aim of guaranteeing the astronaut's adaptation, safety and performance during future space flights.